Chemical Analysis of Eruca sativa Ethanolic Extract and Its Effects on Hyperuricaemia - Arthur Ferrari Teixeira; Jacqueline de Souza; Douglas Daniel Dophine; José Dias de Souza Filho; Dênia Antunes Saúde-Guimarães (Molecules, 2022)
In vivo assays and chemical analyses were performed on the ethanolic extract from leaves of Eruca sativa. UHPLC-ESI-QTOF analysis confirmed the presence of glucosinolates and flavonol glucosides. The major flavonoid of the ethanolic extract, kaempferol-3,4′-di-O-β-glucoside, was isolated, a HPLC-DAD method developed and validated to quantify its content in the extract. In vivo experiments were carried out on Wistar rats with hyperuricaemia induced by potassium oxonate and uric acid. A hypouricaemic effect was observed in hyperuricaemic Wistar rats treated with ethanolic extract at dose of 125 mg/kg and kaempferol-3,4′-di-O-β-glucoside at dose of 10 mg/kg. The main anti-hyperuricaemic mechanism observed in the extract was uricosuric. Kaempferol-3,4′-di-O-β-glucoside was identified as an important component responsible for the total activity of the ethanolic extract and was considered as a good chemical and biological marker of the ethanolic extract of E. sativa. The obtained results indicated the potential of E. sativa in the treatment of hyperuricaemia and its comorbidities.